TRAINING FACTORS FOR EMPLOYEES - Bryan Andri; Wardana; Solihah (Yayasan Putra Adi Dharma, 2023)
The Influence of Training Instructors, Training Participants, Training Materials, Training Methods, and Training Objectives on Employee Performance at PT. Sejahtera Inti Muda Bekasi. The software used to process and analyze the research data is SPSS version 23.0. Based on the results of the analysis and discussion in this study, it can be concluded that: (1) There is a positive and significant influence of training instructors on employee performance. (2) There is a positive and significant influence of training participants on employee performance. (3) There is no influence of training materials on employee performance. (4) There is a positive and significant influence of training methods on employee performance. (5) There is no influence of training objectives on employee performance. (6) There is a positive and significant influence of training instructors, participants, materials, methods, and objectives on the employee performance variable.